Characterization of the tumor immune microenvironment of sinonasal squamous‐cell carcinoma. Issue 1 (12th September 2021) - Gu, Jeffrey T.; Claudio, Natalie; Betts, Courtney; Sivagnanam, Shamilene; Geltzeiler, Mathew; Pucci, Ferdinando
Abstract : Background: Treatment and prognosis of sinonasal squamous‐cell carcinoma (SNSCC) have not significantly improved despite improvements in radical therapy. Characterization of the tumor immune microenvironment (TiME) may identify patient subgroups associated with disease recurrence, and provide new biomarkers for improved patient stratification and treatment. Methods: The TiME was quantitatively evaluated by multiplex immunohistochemistry (mIHC) in archived tissue sections from 38 patients with SNSCC, and were assessed for differences between recurrent (n = 20) and nonrecurrent (n = 18) groups. Hierarchical clustering analyses were performed to identify phenotypic TiME subgroups within the cohort and were used to compare survival outcomes. Results: Our mIHC analysis revealed increased T‐cell populations and decreased myeloid‐cell populations in SNSCC patients without recurrent disease, as compared with patients with recurrent disease. Within T‐cell subsets, there was a significantly higher percentage of granzyme B +, T‐bet +, Eomes + T cells, as well as higher proliferation of CD8 + T cells within the nonrecurrent group relative to the recurrent group. Furthermore, immune‐cell complexity profiles of SNSCC revealed hyper– and hypo–T‐cell–inflamed, myeloid‐inflamed, B‐cell–inflamed, and broadly hypoinflamed subtypes not previously identified by gene expression analyses. Our study revealed that presence of either hyper– or hypo–T‐cell–inflamed TiME subtypes were associated with increased survival outcomes as compared with broadly hypoinflamed TiME subtypes ( p = 0.035 and 0.0376, respectively). Conclusions: The TiME of SNSCC reveals distinct subtypes, which may correlate with recurrence and survival outcomes.